Tantangan dan Strategi Kepemimpinan dalam Manajemen Pendidikan Islam di Era Digital - Rojiid Arbi Muhyardho; Imamul Muttaqin (Jurnal Budi Pekerti Agama Islam, 2025)
The transformation of Digital transformation has brought significant changes in Islamic education management, forcing education leaders to face various challenges such as technological adaptation, cultural change, and the need to develop digital competencies. competence development needs. This research aims to identify the main challenges faced in Islamic education management in the digital era and formulate strategies to overcome these challenges. strategies to overcome these challenges. The methods used in method used in this research is a literature study and in-depth interviews with leaders of Islamic Islamic education institutions. The results showed that effective leadership in the digital era effective leadership in the digital era requires high adaptability, the application of appropriate technology, and the strengthening of Islamic values in the learning process. appropriate technology, as well as strengthening Islamic values in the learning process. The proposed strategies include digital capacity building, innovations in learning, and further collaboration with various stakeholders. stakeholders. In conclusion, Islamic education leaders need to be flexible and innovative in the face of change, while maintaining Islamic values. Islamic values. This study recommends the implementation of more effective strategies and encourages further effective strategies and encourages further research to support the transformation of Islamic education in the future.